Interleukin-2 Receptor Serum Concentrations in Normal Pregnancy and Pre-Eclampsia - Romero Adrián, Tania; Ruíz, Ana; Molina Vílchez, Rafael; Estévez, Jesús; Atencio, Ricardo (Investigación Clínica, 2009)
The purpose of this research was to assess interleukin-2 receptor serum levels in normal pregnancy and pre-eclampsia. Sera from 90 healthy pregnant women (30 for each trimester), 30 with pre-eclampsia and a group of 30 healthy non-pregnant were analyzed. Soluble interleukin-2 receptor was measured by specific double antibody enzymatic immunoassay (ELISA). Results were: 267.5 Ó 12.3 (mean Ó s.e.m) pg/mL in the uncomplicated first trimestre sample, 300.9 Ó 14.5 pg/mL in the second trimester and 248.8 Ó 12.5 pg/mL in the third. The non-pregnant control group had 443.7 Ó 39.6 pg/mL, significantly different from normal pregnancy in all trimesters (p < 0.001). The concentration in pre-eclamptic patients was 382.2 Ó 24.2 pg/mL, with p < 0.01 with regard to the normal third trimester group. The conclusion is that interleukin-2 receptor serum levels diminish in normal pregnancy and rise in preeclampsia. The first finding seems to be a protective mechanism to the fetal allograft. The latter, point to increased cellular activity